METHODS OF REGULAR STORAGE OF VARIETY HASHAKI BEETS “UZBEKISTAN-83” AND “HOSILDOR” (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
If it is preferable to keep beets dry in livestock farms, beets can be stored in crates or thermally insulated warehouses. Storage in deep excavations is less recommended, as these storage conditions are often not very beneficial. There are a number of challenges that this process creates, such as storage, unloading of beets, difficulty in loading machines, and new designs require high investment, so this article provides information on ways to save beets in a cheap and high-quality manner.